2010
DOI: 10.1177/0194599810392173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palatal Implants on Continuous Positive Airway Pressure and Compliance

Abstract: Objective. Determine if the Pillar palatal implant system reduces continuous positive airway pressure (CPAP) pressure and improves patient compliance with CPAP therapy.Study Design. Randomized, double-blind, placebo-controlled study.Setting. Four geographically dispersed tertiary sleep disorder referral centers.Methods. Subjects with mild to moderate sleep apnea dissatisfied with CPAP because of pressure-related complaints were randomized to receive Pillar implants or a sham procedure performed in double-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…Eight studies were excluded due to lack of a comparison of pre- and postoperative CPAPs in patients after UAS. Of the 11 studies that met the inclusion criteria, 5 were retrospective [8,16,17,18,19], 4 were prospective [20,21,22,23], and 2 were RCTs [24,25]. UAS performed in the studies included nasal valve repair, radiofrequency ablation to the palate, turbinate reduction, septoplasty, Pillar implants, tonsillectomy, and UPPP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies were excluded due to lack of a comparison of pre- and postoperative CPAPs in patients after UAS. Of the 11 studies that met the inclusion criteria, 5 were retrospective [8,16,17,18,19], 4 were prospective [20,21,22,23], and 2 were RCTs [24,25]. UAS performed in the studies included nasal valve repair, radiofrequency ablation to the palate, turbinate reduction, septoplasty, Pillar implants, tonsillectomy, and UPPP.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated CPAP adherence in a control and posttreatment group, or preoperative and postoperative use within the same group [18,21,24,25]. Overall, 80 patients still requiring CPAP after surgery were evaluated after Pillar implants (n = 47), UPPP alone or in combination with a multilevel procedure (n = 16), or inferior turbinate reduction (n = 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other trials, a palatal implant delivery system was prepared by the manufacturer to either contain the implant or not, which allowed for blinding of surgeons 17, 18 .…”
Section: Blinding Of Patients Surgeons Outcome Assessors and Caregimentioning
confidence: 99%
“…But others found no significant change in AHI [169]. A recent study showed that pillar implants may subjectively improve CPAP satisfaction, but failed to show any improvement in the compliance of CPAP or in reduction of CPAP pressure [175]. Therefore, pillar implants cannot be recommended and may only be considered in patients with mild to moderate OSA who cannot tolerate or failed other conservative approaches.…”
Section: Soft Palatal Implantsmentioning
confidence: 99%